Problem-based learning in physical education and sport: a systematic review of implementation approaches, learning outcomes, and contextual determinants - Gemi Candra; Jeki Haryanto (Global Econedu, 2025)
Problem-Based Learning (PBL) is a student-centred strategy with the potential to foster higher-order thinking and active engagement, yet its use in physical education (PE) and sport remains limited and fragmented across contexts. This systematic review of literature comprehensively analyzes primary research works to establish how PBL has been implemented in PE and sport-related educational settings, what learning results it yields, and which environmental factors influence its use. PRISMA 2020 was the review guideline, and it was based on a formal Scopus search which initially identified 214 records. After the exclusion of news, reviews and non-English documents, screening for title and abstract, assessment of full texts against the set criteria, a total of 12 studies published from 2021 to 2025 were included in the review. The thematic analysis showed that PBL is being implemented through various modes, some of which include technology-backed tactical simulations and teacher-training projects. The principal results of PBL are the enhancement of motor skills, tactical decision-making, critical thinking, teamwork, and engagement. However, the realization of PBL results was found to be dependent on readiness of teachers, time, and curriculum support. The article develops sport pedagogy by charting PBL implementation and outcomes, giving practical orientation for teachers and coaches, and urging for larger, longer-term and rigorously designed studies.